The Effect Of Communicative Approach On Students' Speaking Ability Indonesian Language In Class Iv Elementary School Barru District - Sri Darmayanti, Tarman A. Arif (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
This study aims to describe the learning process of fourth grade students before applying the communicative approach, describe the fourth grade students' speaking skills after applying the communicative approach, and describe the effect of applying the communicative approach to the fourth grade students' speaking skills in Indonesian language learning in Barru District Elementary School.The results showed a very large influence on students' speaking ability in the experimental class using a communicative approach than in the conventional class. From the results of these data shows that using the communicative method the results of students' speaking abilities are greater. The analysis was carried out and it has been statistically tested that tcount is greater than ttable (10.2 2.0399) which causes Ho to be rejected and H1 to be accepted. So that there is an influence between the speaking ability of students who use a communicative approach and those who do not use a communicative approach in the fourth grade of SD Barru Regency.